Todos aprendem matemática - Costa, Jefferson Martins [UNESP]; Morello, Nadielli Aparecida [UNESP]; Araújo, Ana Paula de [UNESP]; Oliveira, Raquel Gomes de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Everyone learns Mathematics is a project that began in 2014 through a partnership between LAR FILOMENA SANTA and FCT-UNESP. The project seeks to reduce difficulties of children and youth in Mathematics it sought to contribute, through collaborative work, to overcome the gap of learning basic contents of Mathematics presented by children and young people in the LAR, aiming to empower participants, aged between 12 and 15 years to before their learning mathematics, can contribute to the learning of other children attending the LAR. The project aims to 3 items; 1) identify problems of children and young people with the basic mathematical concepts; 2) enable them to take ownership of the intervention of the methodology so that it can be continued in the sense that they will be the guardians of other children in mathematics study process and 3) collect Math books and teaching materials, and initiate a library for LAR SANTA FILOMENA. The project main feature is to provide opportunity for participants to "do math", with the encouragement the fact that they can later contribute to mathematics learning of other children under that their ages. Weekly in LAR SANTA FILOMENA are developed educational activities using appropriate teaching materials for teaching and learning basic mathematical concepts.

Todos aprendem Matemática é um projeto que teve início em 2014, a partir da parceria entre o LAR SANTA FILOMENA e a FCT-UNESP, buscando diminuir dificuldades de crianças e jovens em Matemática, que frequentam o LAR e contribuir, através de trabalhos colaborativos, para a superação da defasagem da aprendizagem de conteúdos básicos de Matemática dos mesmos. O objetivo geral é capacitar os participantes, com idades entre 12 e 15 anos para poderem contribuir com o aprendizado de outras crianças que frequentam o LAR. O projeto tem como objetivos específicos: 1) identificar dificuldades das crianças e jovens quanto a conceitos matemáticos básicos; 2) capacitá-los para que se apropriem da metodologia da intervenção a fim de que esta possa ter continuidade, no sentido de que eles venham a ser os tutores de outras crianças nos processos de estudo da Matemática; 3) arrecadar livros e materiais didáticos de Matemática, e dar início a uma biblioteca para o LAR SANTA FILOMENA. A principal característica do projeto é oferecer oportunidade para que os participantes possam “fazer matemática”, tendo como incentivo o fato de poderem posteriormente contribuir com o aprendizado de Matemática de outras crianças com idades inferiores das suas. Semanalmente no LAR SANTA FILOMENA são desenvolvidas atividades didáticas utilizando-se material pedagógico apropriado para o ensino e aprendizagem de conceitos matemáticos elementares.
Keywords: Mathematics; University extension; Social inclusion; Everyone learns mathematics is an extension; Matemática|Extensão universitária; Inclusão social